(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article provides a legal and theoretical analysis of the objective side of crimes related to the manufacture, distribution, advertising, and demonstration of products that promote potent substances not classified as narcotics, their analogues, or psychotropic substances, as well as the illegal circulation of such substances or toxic substances. According to the theory of criminal law, one of the essential elements of a crime is its objective side. The article analyzes the actions covered by Article 2511 of the Criminal Code, such as the production, distribution, advertisement, and demonstration of products promoting potent substances, or the illegal handling of such substances and toxic materials. The article details specific actions that constitute the objective side of the crime: preparation of products, distribution, advertisement, demonstration, and the manufacturing, storage, transportation, delivery, or transfer of such substances. Particular attention is paid to how these actions are carried out through mass media, social networks, and the Internet for propaganda and promotional purposes. The article also explains how such promotional products affect public consciousness, and discusses the social danger and legal consequences of these crimes. Identifying the objective side of the crime allows for accurate legal qualification, prevention of such acts, and the application of effective legal measures.